Laying down of gold nanorods monolayers on solid surfaces for surface enhanced Raman spectroscopy applications. Issue 47 (24th November 2021) - Zhao, Haidong; Isozaki, Katsuhiro; Taguchi, Tomoya; Yang, Shengchun; Miki, Kazushi
Abstract : Laying-down gold nanorods (GNRs) of a monolayer immobilized on a solid substrate was realized with a hybrid method, a combination of three elemental technologies: self-assembly, electrophoresis, and solvent evaporation. Abstract : Laying-down gold nanorods (GNRs) of a monolayer immobilized on a solid substrate was realized with a hybrid method, a combination of three elemental technologies: surface modification, electrophoresis, and solvent evaporation. The self-assembly of CTAB-protected GNRs in the solution was induced by 0.05 mM of EDTA. The assembled GNRs were deposited in a laying-down form on the solid surface during the hybrid method. The final coverage was over 71% on the substrate with an area larger than 0.6 cm 2 . The spacing between the sides of the GNRs was fixed to be 4.6 ± 0.9 nm by the thermal annealing-promoted crystalline packing of the bilayer of CTAB salt-bridged with EDTA. The obtained laying-down GNRs of a monolayer on the gold substrate show a small shift of the transverse LSPR around 550–570 nm (with a width of around 100 nm) and a large red shift of the longitudinal LSPR to be 900–1050 nm (with a width of 500 nm), because of the strong electromagnetic coupling between the GNRs and gold substrate. Therefore it can be used in a wide range of wavelengths for surface enhanced Raman spectroscopy (SERS) applications. The film has a high enhancement factor with 10 5 for R6G.